Reactive routing protocol is one of the most important parameters in MANET, so a study of their performance is done in the next sub sections using NS2 - MOHAMMED ALAWADI (Al-Rafidain Journal of Computer Sciences and Mathematics)
Mobile ad hoc network is a creation of portable devices; they create a network with infrastructure on the fly that are ever changing. As in the previous network structure, each node performs both the action of a router and a host. Also, nodes cannot be fixed in the network; they can join or leave the network, and this increases the flexibility of the connectivity. There are routing protocols which are used for identification of efficient paths between the nodes in the network so as to seek the determination of the best routes between two nodes. This research show that routing is complex in MANETs and hence it demands the fine tuning of numerous routing protocols. We evaluate the effectiveness of these protocols by analyzing two primary metrics: are the average figures of throughput and average end to end delay. Simulation of this protocol was done using NS2 (Network Simulator) 2. 35, we investigate how well routing protocols fare in terms of different aspects including Size of the packets and number of nodes present